Incidencia en la motricidad fina en las dificultades de la pre-escritura en los niños/as de primer año de educación básica de la escuela Manuel Benjamín Carrión Mora de la ciudad de Machala, periodo lectivo 2013 - 2014. - Iñaguazo Jordan, Sonia Victoria (2015)
School age present characteristics that are linked to the development of strategies to promote fine motor skills, this helps children / as to complete the writing process and allows teachers to generate new knowledge in a dynamic and effective manner.